Digital Transformation: Opportunities and Challenges for Leaders in the Emerging Countries in Response to Covid-19 Pandemic - Thanh Nguyen Hai; Quang Nguyen Van; Mai Nguyen Thi Tuyet (Emerging Science Journal, 2021)
Digital transformation is in a period of strong development, playing an important role in the development of public and private organizations. Its implications are still being clarified. However, up to now, the category of digital transformation has many different conceptions. Therefore, the objective of the paper contributes to the interpretation and discovery of the perception of digital transformation, the cognitive development of digital transformation, the positive aspects of the digital transformation process, the achievements achieved, the urgency of the digital transformation before the impact of the Covid-19 pandemic and challenges and limitations in the initiative of the contingent of civil servants and leaders in the digital transformation process. The research method is mainly based on the available documents from journals, books, research works, and the views of the authors expressed on the websites as a basis for making the analysis evaluate. The discoveries in the research will contribute to building the theoretical basis and direction in making some suggestions for leaders. In practical terms, research has shown that digital transformation can be a challenge, but perceive and prepare for leadership thinking innovation that drives successful digital transformation across countries, especially emerging countries is essential. Doi: 10.28991/esj-2021-SPER-03 Full Text: PDF